Techniken der Täuschung Eine Kultur- und Mediengeschichte der Bühnenzauberkunst im späten neunzehnten Jahrhundert - Rein, Katharina (Büchner-Verlag, 2020)
Katharina Rein's award-winning dissertation in cultural studies is devoted to stage magic in the period from 1860 to 1910 characterized by scientific and technical innovation as well as by a flourishing media culture, the upheavals of industrialization, and the experiences of globalization and colonialism. Modern stage magic does not claim any supernatural effect, but rather presents technically generated illusions, whose modes of operation, however, it conceals. It thus represents a specific form of media use that excessively exhibits media effects while making the technical events behind them disappear. The analysis of four paradigmatic large-scale illusions (»Pepper's Ghost«, »The Vanishing Lady«, levitation and telepathy illusions) opens up glimpses into the hitherto largely unwritten history of magic in the late 19th century. At the same time, this opens up the view of drastic cultural changes and innovations that found their way into this modern, highly technical form of magic. A color picture section and an index of persons and keywords complete the volume.